2015
DOI: 10.1016/j.neulet.2015.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute transcranial direct current stimulation in hot and cold working memory tasks in healthy and depressed subjects

Abstract: Dorsolateral prefrontal cortex (DLPFC) hypoactivity and subcortical hyperactivity have been associated to cognitive impairment for non-emotional ("cold") and emotional ("hot") working memory tasks in major depressive disorder (MDD). We investigated whether an increase of DLPFC activity using transcranial direct current stimulation (tDCS) would differently influence the performance in working memory tasks in depressed and healthy subjects. Forty young adult participants (20 with MDD and 20 healthy controls) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 25 publications
(35 reference statements)
0
23
0
1
Order By: Relevance
“…Finally, our participants received active tDCS at a current density of 0.06 mA/cm 2 for 40 min. This is twice as long as it has been typical of behavioral studies, although periods of 30 min and longer [ 32 , 38 , 40 , 41 , 79 83 ] are becoming common in recent years, especially in studies of cognition. Longer stimulation periods seem to more effectively modulate WM [ 62 ], current density greater than 0.029 mA/cm 2 is positively correlated with greater effects on WM [ 62 ], and total charge delivered is positively correlated with effect size in studies of cognition [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our participants received active tDCS at a current density of 0.06 mA/cm 2 for 40 min. This is twice as long as it has been typical of behavioral studies, although periods of 30 min and longer [ 32 , 38 , 40 , 41 , 79 83 ] are becoming common in recent years, especially in studies of cognition. Longer stimulation periods seem to more effectively modulate WM [ 62 ], current density greater than 0.029 mA/cm 2 is positively correlated with greater effects on WM [ 62 ], and total charge delivered is positively correlated with effect size in studies of cognition [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antidepressant properties, some research has suggested that tDCS may have beneficial neurocognitive effects in both healthy participants and patients with neuropsychiatric disorders, including unipolar and bipolar depression (Martin et al, 2015; Minchino et al, 2015; Moreno et al, 2015; Oliveira et al, 2013; Pope, Brenton, & Miall, 2015). Specific effects include improvement in neurocognitive functions such as attention, processing speed, learning and memory, and working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Induced changes in tissue excitability can persist over minutes to hours after stimulation (depending on stimulation current, duration and number of sessions), effects that are N-methyl-D-aspartate (NMDA) receptor-dependant, and presumed to reflect changes in synaptic efficacy and plasticity (15,16). Initially used as a tool to induce changes in motor evoked potentials, tDCS has more recently been used to modulate cognition, such as attentional control (17) and working memory (18). Neuroimaging indicates that prefrontal tDCS alters functional activation and connectivity in brain regions that support cognitive function, including regions distal from the stimulating electrodes (19,20) (21).…”
mentioning
confidence: 99%